Biological material self-adhesive hemostatic liquid dressing based on active components of traditional chinese medicine for hemostasis
Patent Information
- Application Number
- CN202611415192.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-12
- Publication Date
- 2026-11-03
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了基于中药止血活性成分的生物材料自黏附止血液体敷料,解决了中药止血活性组合物配置形式单一、液体敷料组分分设不清、湿润组织表面黏附和凝胶保持性能不足的问题
1、本发明通过中药止血活性组合物与载药PLGA微/纳米粒共同加入液体敷料体系,使白芨多糖、三七总皂苷、地榆总鞣质、蒲黄黄酮、侧柏叶黄酮和仙鹤草提取物以直接加入和载药PLGA微/纳米粒加入两种形式参与配方,形成中药止血活性成分配置完整的液体敷料。
Smart Images

Figure CN123024201A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hemostatic dressing technology, specifically to a self-adhesive hemostatic dressing based on biomaterials containing hemostatic active ingredients from traditional Chinese medicine. Background Technology
[0002] Liquid dressings are a type of wound care material that can cover wounds through application, injection, or dripping. Compared to sheet dressings, they are more suitable for irregularly shaped or deeper wound areas. Traditional Chinese medicine hemostatic active ingredients have a basis for application as sources of hemostatic activity. Ingredients such as Bletilla striata polysaccharides, Panax notoginseng total saponins, Sanguisorba officinalis total tannins, Typha orientalis flavonoids, Platycladus orientalis leaf flavonoids, and Agrimonia pilosa extract have compound application value in hemostatic body dressings. However, in existing liquid dressings, active ingredients are mostly added directly, resulting in a relatively simple formulation that makes it difficult to simultaneously meet the needs of direct participation in the formulation and participation through drug-loaded PLGA micro / nanoparticles.
[0003] Biomaterial liquid dressings typically need to maintain coverage on moist tissue surfaces and form a gel structure with a certain degree of integrity at the application site. Current liquid dressings often simply mix adhesive materials, gel-forming materials, and buffering systems, which can easily lead to premature contact between the traditional Chinese medicine hemostatic active composition, polysaccharide materials, and calcium chloride during storage, causing changes in the system's state. Furthermore, the lack of clear grouping relationships between the material components makes it difficult to maintain the relative independence of each raw material before use.
[0004] Furthermore, the surface of moist tissue contains an exudate environment, requiring liquid dressings to maintain properties such as wet adhesion, gelation after mixing, and gel retention after application. Existing liquid dressings, relying on a single material to cover the wound, struggle to simultaneously coordinate the synergistic relationships between the traditional Chinese medicine hemostatic active composition, drug-loaded PLGA micro / nanoparticles, dopamine-modified chitosan, oxidized sodium alginate, tannic acid, calcium chloride, poloxamer 407, and poloxamer 188. Therefore, providing a biomaterial self-adhesive hemostatic dressing with clearly defined raw material ratios and component settings, capable of incorporating the traditional Chinese medicine hemostatic active composition in both direct addition and drug-loaded PLGA micro / nanoparticle addition, is a problem that needs to be solved in this field. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine, which solves the problems of limited formulation of hemostatic active ingredients of traditional Chinese medicine, unclear separation of liquid dressing components, and insufficient adhesion and gel retention performance on moist tissue surfaces.
[0006] To address the above problems, the present invention provides the following technical solution: This invention provides a self-adhesive hemostatic dressing based on hemostatic active ingredients from traditional Chinese medicine, using the following technical solution: A biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine comprises the following raw materials in parts by weight: Traditional Chinese medicine hemostatic active composition: 0.5 parts to 10 parts; Drug-loaded PLGA micro / nanoparticles: 1 to 8 parts; Dopamine-modified chitosan: 0.5 to 4 parts; Poloxamer 407: 12 to 25 servings; Polosham 188: 1 to 5 servings; Glycerin: 1 to 6 parts; Sodium alginate oxide: 0.5 to 5 parts; Tannic acid: 0.1 to 2 parts; Calcium chloride: 0.05 parts to 1 part; Phosphate buffer: 34 to 83.35 parts; The total mass fraction of the raw materials is 100 parts; The traditional Chinese medicine hemostatic active composition comprises the following components in parts by weight: Bletilla striata polysaccharide: 15-45 parts; Total saponins of Panax notoginseng: 8 to 30 parts; Total tannins from Sanguisorba officinalis: 5 to 20 parts; Typhae Flavonoids: 3 to 15 parts; Platycladus orientalis leaf flavonoids: 2 to 12 parts; Agrimonia pilosa extract: 2 to 12 parts; The drug-loaded PLGA micro / nanoparticles are PLGA micro / nanoparticles loaded with the hemostatic active composition of the traditional Chinese medicine.
[0007] By adopting the above technical solution, the traditional Chinese medicine hemostatic active composition serves as the source of active ingredients, the drug-loaded PLGA micro / nanoparticles serve as the carrier of the traditional Chinese medicine hemostatic active composition, the dopamine-modified chitosan participates in adhesion to the moist tissue surface, the oxidized sodium alginate, the tannic acid and the calcium chloride participate in the formation of the gel structure, the poloxamer 407 and the poloxamer 188 participate in the gelation process of the liquid dressing at 37°C, and the glycerol participates in the system state regulation; after the raw materials are combined, a liquid dressing system with active ingredient loading, wet adhesion and gel retention capabilities is formed.
[0008] Preferably, the biomaterial self-adhesive hemostatic dressing is in a three-component form, comprising component A, component B, and component C. Component A, component B, and component C are mixed to obtain the biomaterial self-adhesive hemostatic dressing, wherein: Component A comprises the traditional Chinese medicine hemostatic active composition, the drug-loaded PLGA micro / nanoparticles, the dopamine-modified chitosan, the poloxamer 407, the poloxamer 188, the glycerol, and the phosphate buffer. Component B comprises the oxidized sodium alginate, the tannic acid, and the phosphate buffer solution; Component C comprises the calcium chloride and the phosphate buffer.
[0009] By adopting the above technical solution, the traditional Chinese medicine hemostatic active composition, the polysaccharide material and the calcium chloride are separated into different components, reducing the system state changes caused by premature contact during storage; before use, the components A, B and C are mixed so that the components A, B and C enter the same system.
[0010] Preferably, component A, component B, and component C are prepared and mixed under the following conditions: The concentration of the phosphate buffer solution is 0.005 mol / L to 0.02 mol / L; Component A is obtained by stirring at 0℃~10℃ for 0.5h~3h; Component B is obtained by stirring at 0℃~10℃ for 0.5h~3h; Component C is a calcium chloride solution with a mass concentration of 1.55% to 9.33%; The volume ratio of component A, component B and component C is 1:(0.5-1.5):(0.05-0.3), the mixing time is 1 min to 3 min, and the pH after mixing is 5.8 to 7.2.
[0011] By adopting the above technical solution, the concentration of the phosphate buffer solution, the low-temperature stirring conditions, the concentration of the calcium chloride solution, the volume ratio of component A, component B and component C, the mixing time and pH jointly define the mixing conditions of the liquid dressing, so that component A, component B and component C form a liquid dressing system with a clear ratio and a clear pH range after mixing.
[0012] Preferably, the Bletilla striata polysaccharide is prepared by the following steps: Take Bletilla striata, grind it into powder, and pass it through a 60-100 mesh sieve; The pulverized and sieved Bletilla striata medicinal material is mixed with purified water at a mass ratio of 1:(6-20), and extracted at 60℃-90℃ for 1-3 hours, 1-3 times, and filtered to obtain Bletilla striata medicinal material filtrate. The filtrate of Bletilla striata is concentrated under reduced pressure at 40℃~50℃ to 1 / 5~1 / 3 of the volume of the filtrate of Bletilla striata to obtain a concentrated Bletilla striata extract. Add 95% ethanol to the concentrated Bletilla striata extract to make the final ethanol volume fraction 60%–80%. Let it stand at 2℃–8℃ for 6h–24h, centrifuge, collect the Bletilla striata precipitate, and dry the precipitate at 40℃–50℃ for 6h–10h to obtain the Bletilla striata polysaccharide.
[0013] By adopting the above technical solution, the Bletilla striata medicinal material is extracted with water, concentrated under reduced pressure and precipitated with ethanol to obtain the Bletilla striata polysaccharide, so that the Bletilla striata polysaccharide enters the liquid dressing system as the polysaccharide component in the traditional Chinese medicine hemostatic active composition.
[0014] Preferably, the traditional Chinese medicine hemostatic active composition is prepared by the following steps: Take Panax notoginseng, Sanguisorba officinalis, Typha pollen, Platycladus orientalis leaves and Agrimonia pilosa herbs respectively, pulverize them and pass them through a 60-100 mesh sieve; The pulverized and sieved Panax notoginseng, Sanguisorba officinalis, Typha pollen, Platycladus orientalis leaves, and Agrimonia pilosa herbs were respectively mixed with an ethanol aqueous solution with a volume fraction of 30% to 80% at a mass ratio of 1:(6 to 20), and extracted at 40℃ to 80℃ for 1 to 4 hours, 1 to 3 times, and filtered to obtain Panax notoginseng filtrate, Sanguisorba officinalis filtrate, Typha pollen filtrate, Platycladus orientalis leaf filtrate, and Agrimonia pilosa filtrate, respectively. The filtrate of Panax notoginseng, the filtrate of Sanguisorba officinalis, the filtrate of Typha pollen, the filtrate of Platycladus orientalis leaf, and the filtrate of Agrimonia pilosa were concentrated under reduced pressure at 40℃ to 55℃, and dried at 40℃ to 55℃ for 6h to 10h, respectively, to obtain the total saponins of Panax notoginseng, the total tannins of Sanguisorba officinalis, the flavonoids of Typha pollen, the flavonoids of Platycladus orientalis leaf, and the extract of Agrimonia pilosa. The Bletilla striata polysaccharide, Panax notoginseng total saponins, Sanguisorba officinalis total tannins, Typha orientalis flavonoids, Platycladus orientalis leaf flavonoids and Agrimonia pilosa extract are mixed for 30 min to 60 min to obtain the traditional Chinese medicine hemostatic active composition.
[0015] By adopting the above technical solution, the Bletilla striata polysaccharide, the Panax notoginseng total saponins, the Sanguisorba officinalis total tannins, the Typha orientalis flavonoids, the Platycladus orientalis leaf flavonoids, and the Agrimonia pilosa extract are combined in a limited proportion so that the polysaccharide, saponin, tannin, flavonoid and extract components together constitute the traditional Chinese medicine hemostatic active composition.
[0016] Preferably, the dopamine-modified chitosan is prepared by the following steps: Carboxymethyl chitosan and MES buffer solution with a concentration of 0.05 mol / L to 0.2 mol / L were mixed at a mass ratio of 0.5:99.5 to 3.0:97.0 to prepare a carboxymethyl chitosan solution with a mass concentration of 0.5% to 3.0%. Adjust the pH of the carboxymethyl chitosan solution to 4.5–6.0, and purge with N2 for 10–30 minutes; Dopamine hydrochloride is added to the carboxymethyl chitosan solution after N2 purging, wherein the mass ratio of dopamine hydrochloride to carboxymethyl chitosan is 0.05 to 0.5:1; 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added, with the molar ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and dopamine hydrochloride being (0.8-1.5):(0.8-1.5):1. The mixture was reacted at 15℃-35℃ in the dark for 6-24 hours to obtain a dopamine-modified chitosan reaction solution.
[0017] By adopting the above technical solution, the carboxymethyl chitosan, the dopamine hydrochloride, the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and the N-hydroxysuccinimide are reacted in the MES buffer to obtain the dopamine-modified chitosan reaction solution.
[0018] Preferably, the dopamine-modified chitosan reaction solution is treated with the following steps: The dopamine-modified chitosan reaction solution was placed in a dialysis bag with a molecular weight cutoff of 3500 Da to 14000 Da, and dialyzed with purified water for 24 h to 72 h to obtain dopamine-modified chitosan dialysis solution. The volume ratio of purified water to the dopamine-modified chitosan reaction solution is 50:1 to 100:1, and the purified water is replaced every 6 to 12 hours. The dopamine-modified chitosan dialysis solution was pre-frozen at -60℃ to -20℃ for 6h to 24h and freeze-dried for 12h to 36h to obtain the dopamine-modified chitosan.
[0019] By adopting the above technical solution, the dopamine-modified chitosan reaction solution is subjected to dialysis, pre-freezing and freeze-drying to obtain the dopamine-modified chitosan, which is then added to component A as a raw material.
[0020] Preferably, the oxidized sodium alginate is prepared by the following steps: Sodium alginate and purified water were mixed at a mass ratio of 0.5:99.5 to 2.5:97.5 to prepare a sodium alginate solution with a mass concentration of 0.5% to 2.5%. Adjust the pH of the sodium alginate solution to 6.0–7.0; Sodium periodate was added to the sodium alginate solution after pH adjustment, wherein the molar ratio of sodium periodate to sodium alginate uronic acid units was 0.05 to 0.25:1, and the reaction was carried out at 15°C to 30°C in the dark for 2 to 10 hours. Ethylene glycol was added to terminate the reaction, wherein the molar ratio of ethylene glycol to sodium periodate was 1.5 to 3:1, and the reaction termination time was 0.5 h to 2 h, to obtain sodium alginate oxidized reaction solution; The sodium alginate oxidized reaction solution was placed in a dialysis bag with a molecular weight cutoff of 3500 Da to 14000 Da, dialyzed with purified water for 24 h to 72 h, and then freeze-dried for 12 h to 36 h to obtain the sodium alginate oxidized solution.
[0021] By adopting the above technical solution, the sodium alginate reacts under the action of sodium periodate, and is terminated by ethylene glycol, dialyzed and freeze-dried to obtain the oxidized sodium alginate, so that the oxidized sodium alginate participates in the formation of the gel structure after mixing as a polysaccharide material in the B component.
[0022] Preferably, the drug-loaded PLGA micro / nanoparticles are prepared by the following steps: The hemostatic active composition of the traditional Chinese medicine was mixed with purified water at a mass ratio of 1:99 to 5:95 to prepare an internal aqueous phase with a mass concentration of 1% to 5%. Mix PLGA with ethyl acetate to prepare an organic phase with a mass concentration of 2% to 6%; The mass ratio of the traditional Chinese medicine hemostatic active composition to the PLGA is 1:10 to 1:2, and the volume ratio of the internal aqueous phase to the organic phase is 1:10 to 1:2. The aqueous phase is added to the organic phase, and ultrasonic emulsification is performed under ice bath conditions. The ultrasonic power is 100W to 300W, and the ultrasonic emulsification time is 5min to 15min to obtain the primary emulsion.
[0023] By adopting the above technical solution, the traditional Chinese medicine hemostatic active composition is dispersed in the internal aqueous phase, the PLGA is dispersed in the organic phase, and the internal aqueous phase and the organic phase are ultrasonically emulsified to obtain the primary emulsion, so that the traditional Chinese medicine hemostatic active composition enters the preparation process of the drug-loaded PLGA micro / nanoparticles.
[0024] Preferably, the colostrum is processed through the following steps: The primary emulsion was added to a polyvinyl alcohol aqueous solution with a mass concentration of 0.5% to 3.0%, wherein the volume ratio of the polyvinyl alcohol aqueous solution to the organic phase was 5:1 to 20:1. Shear emulsification was carried out under ice bath conditions at a rotation speed of 6000 rpm to 14000 rpm and a shear emulsification time of 0.5 h to 2 h to obtain a secondary emulsion. The re-emulsion was stirred at 25℃~30℃ for 2h~6h, then centrifuged at 8000rpm~12000rpm for 10min~20min. The supernatant was discarded, the precipitate was collected, and the precipitate was washed three times with purified water and freeze-dried for 12h~36h to obtain the drug-loaded PLGA micro / nanoparticles.
[0025] By adopting the above technical solution, the primary emulsion is sheared and emulsified by the polyvinyl alcohol aqueous solution to form the secondary emulsion. The secondary emulsion is stirred, centrifuged, washed and freeze-dried to obtain the drug-loaded PLGA micro / nanoparticles, so that the traditional Chinese medicine hemostatic active composition is added to component A in the form of the drug-loaded PLGA micro / nanoparticles.
[0026] This invention provides a self-adhesive hemostatic dressing based on hemostatic active ingredients from traditional Chinese medicine. It has the following beneficial effects: 1. This invention involves adding a traditional Chinese medicine hemostatic active composition to a liquid dressing system together with drug-loaded PLGA micro / nanoparticles. This allows the polysaccharides of Bletilla striata, total saponins of Panax notoginseng, total tannins of Sanguisorba officinalis, flavonoids of Typha orientalis, flavonoids of Platycladus orientalis leaf, and extract of Agrimonia pilosa to participate in the formulation in two forms: direct addition and addition of drug-loaded PLGA micro / nanoparticles, thus forming a liquid dressing with a complete formulation of traditional Chinese medicine hemostatic active ingredients.
[0027] 2. In this invention, components A, B, and C are set separately and mixed before use. This allows the hemostatic active composition of traditional Chinese medicine, drug-loaded PLGA micro / nanoparticles, dopamine-modified chitosan, oxidized sodium alginate, tannic acid, calcium chloride, and phosphate buffer to be set in different components before mixing. After mixing, they enter the same liquid dressing system, and the correspondence between each raw material is clearly maintained.
[0028] 3. This invention combines dopamine-modified chitosan, oxidized sodium alginate, tannic acid, calcium chloride, poloxamer 407, and poloxamer 188 to make the liquid dressing contain the raw materials related to self-adhesive hemostatic dressings. Glycerin and phosphate buffer are also involved in forming a liquid dressing system with a clear ratio of raw materials, a clear component setting, and complete compatibility with the hemostatic active composition of traditional Chinese medicine. Attached Figure Description
[0029] Figure 1 This is a rheological frequency scan of the liquid dressing of the present invention after it has been mixed into a gel. Figure 2 This is the ultraviolet-visible absorption spectrum of the liquid dressing release solution of the present invention; Figure 3 This is a rheological frequency scan of the liquid dressing of the present invention after treatment with simulated wound exudate. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0032] Bletilla striata polysaccharide is a water-extracted and alcohol-precipitated polysaccharide derived from Bletilla striata, with a total sugar content ≥70%, moisture content ≤10%, and a number-average molecular weight of 1×10⁻⁶. 4 ~5×10 5 Da, whose main sugar residues include glucose residues and mannose residues.
[0033] Panax notoginseng total saponins are total saponin extracts derived from Panax notoginseng, with a total saponin content ≥80%. The main indicator components include notoginseng saponin R1, ginsenoside Rg1 and ginsenoside Rb1, and moisture content ≤8%.
[0034] The total tannins of Sanguisorba officinalis are tannin extracts derived from Sanguisorba officinalis, with a total tannin content of ≥50% (calculated as gallic acid) and a moisture content of ≤8%.
[0035] Typhae pollen flavonoids are flavonoid extracts derived from Typhae pollen, with a total flavonoid content of ≥40% (calculated as rutin) and a moisture content of ≤8%.
[0036] Platycladus orientalis leaf flavonoids are flavonoid extracts derived from Platycladus orientalis leaves, with a total flavonoid content of ≥30% (calculated as rutin) and a moisture content of ≤8%.
[0037] Agrimony extract is an extract derived from Agrimony, with an extraction ratio of 10:1. The total phenol content (calculated as gallic acid) is ≥10%, and the moisture content is ≤8%.
[0038] Carboxymethyl chitosan, CAS No. 83512-85-0, has a number average molecular weight of 50,000 to 300,000 Da, a degree of deacetylation of ≥80%, and a degree of carboxymethyl substitution of 60% to 95%.
[0039] Dopamine hydrochloride, CAS number 62-31-7, chemical name 4-(2-aminoethyl)benzene-1,2-diol hydrochloride, molecular formula C8H 11 NO2·HCl, purity ≥98%.
[0040] 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl), CAS No. 25952-53-8, molecular formula C8H 17 N3·HCl, purity ≥98%.
[0041] N-hydroxysuccinimide (NHS), CAS No. 6066-82-6, molecular formula C4H5NO3, purity ≥98%.
[0042] 2-(N-morpholino)ethanesulfonic acid (MES), CAS No. 4432-31-9, molecular formula C6H 13 NO4S is used to prepare MES buffer.
[0043] Sodium alginate, CAS No. 9005-38-3, has a viscosity of 100-300 mPa·s in a 1% aqueous solution at 25°C.
[0044] Sodium periodate, CAS No. 7790-28-5, chemical formula NaIO4, purity ≥99%.
[0045] Ethylene glycol, CAS No. 107-21-1, molecular formula C2H6O2, purity ≥99%.
[0046] Poly(D,L-lactic-co-hydroxyacetic acid) (PLGA), CAS No. 26780-50-7, lactic acid / hydroxyacetic acid molar ratio is 75:25, number average molecular weight is 20,000 to 50,000 Da, and molecular weight distribution PDI ≤ 2.0.
[0047] Polyvinyl alcohol (PVA), CAS No. 9002-89-5, has a degree of alcoholysis of 87.0% to 89.0% and a number-average molecular weight of 30,000 to 70,000 Da.
[0048] Poloxamer 407, CAS No. 9003-11-6, has an average molecular weight of 9840–14600 Da.
[0049] Poloxamer 188, CAS No. 9003-11-6, has an average molecular weight of 7680-9510 Da.
[0050] Tannic acid, CAS number 1401-55-4, its molecular formula is usually represented as C 76 H 52 O 46 Content ≥90%.
[0051] Calcium chloride, CAS No. 10043-52-4, chemical formula CaCl2, is made of anhydrous calcium chloride with a content ≥96%.
[0052] Glycerol, CAS No. 56-81-5, chemical name is glycerol, molecular formula is C3H8O3, content ≥99%.
[0053] Ethyl acetate, CAS No. 141-78-6, molecular formula C4H8O2, is used as an organic solvent for dissolving PLGA.
[0054] Preparation Example 1: This preparation example provides a traditional Chinese medicine hemostatic active composition A1, comprising the following steps: Take Bletilla striata medicinal material, pulverize it and pass it through a 60-mesh sieve. Mix Bletilla striata medicinal material with purified water at a mass ratio of 1:6, extract at 60℃ for 1 hour, and repeat the extraction once. Filter the mixture, and concentrate the filtrate under reduced pressure at 40℃ to 1 / 3 of the filtrate volume. Add 95% ethanol to the concentrate, controlling the volume ratio of concentrate to 95% ethanol at 7:12, so that the final ethanol volume fraction is 60%. Let it stand at 2℃ for 6 hours, centrifuge, collect the precipitate, and dry it at 40℃ for 6 hours to obtain Bletilla striata polysaccharide.
[0055] Panax notoginseng, Sanguisorba officinalis, Typha pollen, Platycladus orientalis leaves, and Agrimonia pilosa were taken separately, pulverized, and passed through a 60-mesh sieve. Each herb was mixed with a 30% (v / v) ethanol aqueous solution at a mass ratio of 1:6, extracted at 40℃ for 1 hour, and extracted once. The extracts were filtered, and the filtrates were concentrated under reduced pressure at 40℃ and dried at 40℃ for 6 hours to obtain total saponins of Panax notoginseng, total tannins of Sanguisorba officinalis, flavonoids of Typha pollen, flavonoids of Platycladus orientalis leaves, and Agrimonia pilosa extract.
[0056] Take 15 parts by weight of Bletilla striata polysaccharide, 8 parts by weight of Panax notoginseng total saponins, 5 parts by weight of Sanguisorba officinalis total tannins, 3 parts by weight of Typha orientalis flavonoids, 2 parts by weight of Platycladus orientalis leaf flavonoids and 2 parts by weight of Agrimonia pilosa extract, mix for 30 min to obtain hemostatic active composition A1 of traditional Chinese medicine.
[0057] Preparation Example 2: This preparation example provides a traditional Chinese medicine hemostatic active composition A2, comprising the following steps: Take Bletilla striata medicinal material, pulverize it and pass it through an 80-mesh sieve. Mix Bletilla striata medicinal material with purified water at a mass ratio of 1:12, extract at 75℃ for 2 hours, and repeat the extraction twice. Filter, combine the filtrates, and concentrate the filtrate under reduced pressure at 45℃ to 1 / 4 of the total volume of the filtrate. Add 95% ethanol to the concentrate, controlling the volume ratio of concentrate to 95% ethanol at 5:14, so that the final volume fraction of ethanol is 70%. Let it stand at 4℃ for 12 hours, centrifuge, collect the precipitate, and dry it at 45℃ for 8 hours to obtain Bletilla striata polysaccharide.
[0058] Panax notoginseng, Sanguisorba officinalis, Typha pollen, Platycladus orientalis leaves, and Agrimonia pilosa were taken separately, pulverized, and passed through an 80-mesh sieve. Each herb was mixed with a 55% ethanol aqueous solution at a mass ratio of 1:12 and extracted at 60℃ for 2 hours, twice. After filtration, the corresponding filtrates of each herb were combined, concentrated under reduced pressure at 45℃, and dried at 45℃ for 8 hours to obtain total saponins of Panax notoginseng, total tannins of Sanguisorba officinalis, flavonoids of Typha pollen, flavonoids of Platycladus orientalis leaves, and Agrimonia pilosa extract.
[0059] Take 30 parts by weight of Bletilla striata polysaccharide, 18 parts by weight of Panax notoginseng total saponins, 10 parts by weight of Sanguisorba officinalis total tannins, 8 parts by weight of Typha orientalis flavonoids, 6 parts by weight of Platycladus orientalis leaf flavonoids and 6 parts by weight of Agrimonia pilosa extract, mix for 45 min to obtain hemostatic active composition A2 of traditional Chinese medicine.
[0060] Preparation Example 3: This preparation example provides a traditional Chinese medicine hemostatic active composition A3, comprising the following steps: Take Bletilla striata medicinal material, pulverize it and pass it through a 100-mesh sieve. Mix Bletilla striata medicinal material with purified water at a mass ratio of 1:20, extract at 90℃ for 3 hours, and repeat the extraction 3 times. Filter, combine the filtrates, and concentrate the filtrate under reduced pressure at 50℃ to 1 / 5 of the total volume of the filtrate. Add 95% ethanol to the concentrate, controlling the volume ratio of concentrate to 95% ethanol at 3:16, so that the final volume fraction of ethanol is 80%. Let it stand at 8℃ for 24 hours, centrifuge, collect the precipitate, and dry it at 50℃ for 10 hours to obtain Bletilla striata polysaccharide.
[0061] Panax notoginseng, Sanguisorba officinalis, Typha pollen, Platycladus orientalis leaves, and Agrimonia pilosa were taken separately, pulverized, and passed through a 100-mesh sieve. Each herb was mixed with an 80% ethanol aqueous solution at a mass ratio of 1:20 and extracted at 80℃ for 4 hours, repeated 3 times. After filtration, the corresponding filtrates of each herb were combined, concentrated under reduced pressure at 55℃, and dried at 55℃ for 10 hours to obtain total saponins of Panax notoginseng, total tannins of Sanguisorba officinalis, flavonoids of Typha pollen, flavonoids of Platycladus orientalis leaves, and Agrimonia pilosa extract.
[0062] Take 45 parts by weight of Bletilla striata polysaccharide, 30 parts by weight of total saponins of Panax notoginseng, 20 parts by weight of total tannins of Sanguisorba officinalis, 15 parts by weight of Typha orientalis flavonoids, 12 parts by weight of Platycladus orientalis leaf flavonoids and 12 parts by weight of Agrimonia pilosa extract, mix for 60 min to obtain hemostatic active composition A3 of traditional Chinese medicine.
[0063] Preparation Example 4: This preparation example provides dopamine-modified chitosan B1, including the following steps: Carboxymethyl chitosan and 0.05 mol / L MES buffer were mixed at a mass ratio of 0.5:99.5 to prepare a 0.5% carboxymethyl chitosan solution. The pH was adjusted to 4.5, and N2 was introduced to purge for 10 min.
[0064] Dopamine hydrochloride was added, with a mass ratio of dopamine hydrochloride to carboxymethyl chitosan of 0.05:1; EDC·HCl and NHS were added, with a molar ratio of EDC·HCl, NHS and dopamine hydrochloride of 0.8:0.8:1, and the mixture was reacted at 15°C in the dark for 6 hours.
[0065] The reaction solution was placed in a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed with purified water for 24 hours. The volume ratio of purified water to reaction solution was 50:1, and the purified water was replaced every 6 hours. The dialysate was pre-frozen at -20°C for 6 hours and freeze-dried for 12 hours to obtain dopamine-modified chitosan B1.
[0066] Preparation Example 5: This preparation example provides dopamine-modified chitosan B2, including the following steps: Carboxymethyl chitosan and 0.1 mol / L MES buffer were mixed at a mass ratio of 1.5:98.5 to prepare a 1.5% carboxymethyl chitosan solution. The pH was adjusted to 5.2, and N2 was introduced to purge for 20 min.
[0067] Dopamine hydrochloride was added, with a mass ratio of dopamine hydrochloride to carboxymethyl chitosan of 0.2:1; EDC·HCl and NHS were added, with a molar ratio of EDC·HCl, NHS and dopamine hydrochloride of 1.2:1.2:1, and the mixture was reacted at 25°C in the dark for 12 hours.
[0068] The reaction solution was placed in a dialysis bag with a molecular weight cutoff of 8000 Da and dialyzed with purified water for 48 hours. The volume ratio of purified water to reaction solution was 80:1, and the purified water was replaced every 8 hours. The dialysate was pre-frozen at -40℃ for 12 hours and freeze-dried for 24 hours to obtain dopamine-modified chitosan B2.
[0069] Preparation Example 6: This preparation example provides dopamine-modified chitosan B3, including the following steps: Carboxymethyl chitosan and 0.2 mol / L MES buffer were mixed at a mass ratio of 3.0:97.0 to prepare a 3.0% carboxymethyl chitosan solution. The pH was adjusted to 6.0, and N2 was introduced to purge for 30 min.
[0070] Dopamine hydrochloride was added, with a mass ratio of dopamine hydrochloride to carboxymethyl chitosan of 0.5:1; EDC·HCl and NHS were added, with a molar ratio of EDC·HCl, NHS and dopamine hydrochloride of 1.5:1.5:1, and the mixture was reacted at 35°C in the dark for 24 hours.
[0071] The reaction solution was placed in a dialysis bag with a molecular weight cutoff of 14000 Da and dialyzed with purified water for 72 h. The volume ratio of purified water to reaction solution was 100:1, and the purified water was replaced every 12 h. The dialysate was pre-frozen at -60℃ for 24 h and freeze-dried for 36 h to obtain dopamine-modified chitosan B3.
[0072] Preparation Example 7: This preparation example provides oxidized sodium alginate C1, including the following steps: Sodium alginate and purified water were mixed at a mass ratio of 0.5:99.5 to prepare a sodium alginate solution with a mass concentration of 0.5%, and the pH was adjusted to 6.0.
[0073] Sodium periodate was added to a sodium alginate solution, with a molar ratio of sodium periodate to sodium alginate uronic acid units of 0.05:1, and the reaction was carried out at 15°C in the dark for 2 hours.
[0074] The reaction was terminated by adding ethylene glycol at a molar ratio of 1.5:1 to sodium periodate, with a termination time of 0.5 h. The reaction solution was placed in a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed with purified water for 24 h at a volume ratio of 50:1 (purified water to reaction solution). The purified water was replaced every 6 h. The solution was then freeze-dried for 12 h to obtain sodium alginate oxidized (C1).
[0075] Preparation Example 8: This preparation example provides oxidized sodium alginate C2, including the following steps: Sodium alginate and purified water were mixed at a mass ratio of 1.5:98.5 to prepare a sodium alginate solution with a mass concentration of 1.5%, and the pH was adjusted to 6.5.
[0076] Sodium periodate was added to a sodium alginate solution, with a molar ratio of sodium periodate to sodium alginate uronic acid units of 0.15:1, and the reaction was carried out at 25°C in the dark for 6 hours.
[0077] The reaction was terminated by adding ethylene glycol at a molar ratio of 2:1 to sodium periodate, and the reaction time was 1 hour. The reaction solution was placed in a dialysis bag with a molecular weight cutoff of 8000 Da and dialyzed with purified water for 48 hours at a volume ratio of 80:1 (purified water to reaction solution). The purified water was replaced every 8 hours. The solution was then freeze-dried for 24 hours to obtain sodium alginate oxidized (C2).
[0078] Preparation Example 9: This preparation example provides oxidized sodium alginate C3, including the following steps: Sodium alginate and purified water were mixed at a mass ratio of 2.5:97.5 to prepare a sodium alginate solution with a mass concentration of 2.5%, and the pH was adjusted to 7.0.
[0079] Sodium periodate was added to a sodium alginate solution, with a molar ratio of sodium periodate to sodium alginate uronic acid units of 0.25:1, and the reaction was carried out at 30°C in the dark for 10 hours.
[0080] The reaction was terminated by adding ethylene glycol at a molar ratio of 3:1 to sodium periodate over a period of 2 hours. The reaction solution was placed in a dialysis bag with a molecular weight cutoff of 14000 Da and dialyzed with purified water for 72 hours at a volume ratio of 100:1 (purified water to reaction solution). The purified water was replaced every 12 hours. The solution was then freeze-dried for 36 hours to obtain sodium alginate oxidized (C3).
[0081] Preparation Example 10: This preparation example provides drug-loaded PLGA micro / nanoparticles D1, including the following steps: The hemostatic active composition A1 of traditional Chinese medicine was mixed with purified water at a mass ratio of 1:99 to prepare an internal aqueous phase with a mass concentration of 1%. PLGA and ethyl acetate were mixed to prepare an organic phase with a mass concentration of 2%. The mass ratio of the hemostatic active composition A1 of traditional Chinese medicine to PLGA was 1:10, and the volume ratio of the internal aqueous phase to the organic phase was 1:10.
[0082] The aqueous phase was added to the organic phase, and emulsified under ice bath conditions with 100W ultrasonic power for 5 min to obtain the primary emulsion. The primary emulsion was then added to a 0.5% PVA aqueous solution with a PVA aqueous solution to organic phase volume ratio of 5:1, and sheared under ice bath conditions at 6000 rpm for 0.5 h to obtain the secondary emulsion.
[0083] The double emulsion was stirred at 25°C for 2 hours to evaporate ethyl acetate, then centrifuged at 8000 rpm for 10 minutes, the supernatant was discarded, the precipitate was washed three times with purified water, and freeze-dried for 12 hours to obtain drug-loaded PLGA micro / nanoparticles D1.
[0084] Preparation Example 11: This preparation example provides drug-loaded PLGA micro / nanoparticles D2, including the following steps: The hemostatic active composition A2 of traditional Chinese medicine was mixed with purified water at a mass ratio of 3:97 to prepare an internal aqueous phase with a mass concentration of 3%. PLGA and ethyl acetate were mixed to prepare an organic phase with a mass concentration of 4%. The mass ratio of the hemostatic active composition A2 of traditional Chinese medicine to PLGA was 1:4, and the volume ratio of the internal aqueous phase to the organic phase was 1:5.
[0085] The aqueous phase was added to the organic phase, and emulsified under ice bath conditions with ultrasonic power of 200W for 10 min to obtain the primary emulsion. The primary emulsion was then added to a 1.5% PVA aqueous solution with a PVA aqueous solution to organic phase volume ratio of 10:1, and sheared under ice bath conditions at 10000 rpm for 1 h to obtain the secondary emulsion.
[0086] The double emulsion was stirred at 25°C for 4 h to evaporate ethyl acetate, then centrifuged at 10,000 rpm for 15 min, the supernatant was discarded, the precipitate was washed three times with purified water, and freeze-dried for 24 h to obtain drug-loaded PLGA micro / nanoparticles D2.
[0087] Preparation Example 12: This preparation example provides drug-loaded PLGA micro / nanoparticles D3, including the following steps: The hemostatic active composition A3 of traditional Chinese medicine was mixed with purified water at a mass ratio of 5:95 to prepare an internal aqueous phase with a mass concentration of 5%. PLGA and ethyl acetate were mixed to prepare an organic phase with a mass concentration of 6%. The mass ratio of the hemostatic active composition A3 of traditional Chinese medicine to PLGA was 1:2, and the volume ratio of the internal aqueous phase to the organic phase was 1:2.
[0088] The aqueous phase was added to the organic phase, and emulsified under ice bath conditions with ultrasonic power of 300W for 15 min to obtain the primary emulsion. The primary emulsion was then added to a 3.0% PVA aqueous solution with a PVA aqueous solution to organic phase volume ratio of 20:1, and sheared under ice bath conditions at 14000 rpm for 2 h to obtain the secondary emulsion.
[0089] The double emulsion was stirred at 30°C for 6 h to evaporate ethyl acetate, then centrifuged at 12000 rpm for 20 min, the supernatant was discarded, the precipitate was washed three times with purified water, and freeze-dried for 36 h to obtain drug-loaded PLGA micro / nanoparticles D3.
[0090] Example 1:
[0091] This embodiment provides a biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine, which is prepared through the following steps: Based on a total mass of 100 parts by weight of the final mixed liquid dressing, 0.5 parts by weight of the traditional Chinese medicine hemostatic active composition A1, 1 part by weight of the drug-loaded PLGA micro / nanoparticles D1, 0.5 parts by weight of the dopamine-modified chitosan B1, 12 parts by weight of poloxamer 407, 1 part by weight of poloxamer 188, and 1 part by weight of glycerol were mixed with phosphate buffer solution with a concentration of 0.005 mol / L and stirred at 0°C for 0.5 h to obtain component A; Based on a total mass of 100 parts by weight of the final mixed liquid dressing, 0.5 parts by weight of sodium alginate C1, 0.1 parts by weight of tannic acid, and 0.005 mol / L phosphate buffer were mixed and stirred at 0°C for 0.5 h to obtain component B. Based on a total mass of 100 parts by mass of the final mixed liquid dressing, 0.05 parts by mass of calcium chloride were added to a 0.005 mol / L phosphate buffer solution to prepare a calcium chloride solution with a mass concentration of 1.55%, thus obtaining component C. The total amount of 0.005 mol / L phosphate buffer in components A, B and C was 83.35 parts by mass. Components A, B and C were mixed at a volume ratio of 1:0.5:0.05 for 1 min and the pH was adjusted to 5.8 to obtain a self-adhesive hemostatic dressing based on the hemostatic active ingredients of traditional Chinese medicine.
[0092] Example 2:
[0093] This embodiment provides a biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine, which is prepared through the following steps: Based on a total mass of 100 parts by weight of the final mixed liquid dressing, 5 parts by weight of the traditional Chinese medicine hemostatic active composition A2, 4 parts by weight of the drug-loaded PLGA micro / nanoparticles D2, 2 parts by weight of the dopamine-modified chitosan B2, 20 parts by weight of poloxamer 407, 3 parts by weight of poloxamer 188, and 3 parts by weight of glycerol were mixed with 0.01 mol / L phosphate buffer solution and stirred at 6°C for 2 hours to obtain component A. Based on a total mass of 100 parts by weight of the final mixed liquid dressing, 2.5 parts by weight of sodium alginate C2, 0.8 parts by weight of tannic acid, and 0.01 mol / L phosphate buffer were mixed and stirred at 6°C for 2 hours to obtain component B. Based on a total mass of 100 parts by mass of the final mixed liquid dressing, 0.3 parts by mass of calcium chloride were added to a 0.01 mol / L phosphate buffer solution to prepare a calcium chloride solution with a mass concentration of 6.3%, thus obtaining component C. The total amount of 0.01 mol / L phosphate buffer in components A, B and C was 59.4 parts by mass. Components A, B and C were mixed at a volume ratio of 1:1:0.1 for 2 min and the pH was adjusted to 6.5 to obtain a self-adhesive hemostatic dressing based on the hemostatic active ingredients of traditional Chinese medicine.
[0094] Example 3:
[0095] This embodiment provides a biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine, which is prepared through the following steps: Based on a total mass of 100 parts by weight of the final mixed liquid dressing, 10 parts by weight of the traditional Chinese medicine hemostatic active composition A3, 8 parts by weight of the drug-loaded PLGA micro / nanoparticles D3, 4 parts by weight of the dopamine-modified chitosan B3, 25 parts by weight of poloxamer 407, 5 parts by weight of poloxamer 188, and 6 parts by weight of glycerol were mixed with 0.02 mol / L phosphate buffer solution and stirred at 10°C for 3 h to obtain component A. Based on a total mass of 100 parts by mass of the final mixed liquid dressing, 5 parts by mass of sodium alginate C3, 2 parts by mass of tannic acid, and 0.02 mol / L phosphate buffer were mixed and stirred at 10°C for 3 hours to obtain component B. Based on a total mass of 100 parts by mass of the final mixed liquid dressing, 1 part by mass of calcium chloride was added to a 0.02 mol / L phosphate buffer solution to prepare a calcium chloride solution with a mass concentration of 9.33%, thus obtaining component C. The total amount of 0.02 mol / L phosphate buffer in components A, B and C was 34 parts by mass. Components A, B and C were mixed at a volume ratio of 1:1.5:0.3 for 3 min and the pH was adjusted to 7.2 to obtain a self-adhesive hemostatic dressing based on the hemostatic active ingredients of traditional Chinese medicine.
[0096] Comparative Example 1: Compared with Example 2, the difference is that the traditional Chinese medicine hemostatic active composition A2 is not added, and the drug-loaded PLGA micro / nanoparticles D2 with a content of 4 parts by mass are replaced with blank PLGA micro / nanoparticles with a content of 4 parts by mass. The content is made up to 5 parts by mass with phosphate buffer with a concentration of 0.01 mol / L. All other parameters and steps are the same.
[0097] Comparative Example 2: Compared with Example 2, the difference is that drug-loaded PLGA micro / nanoparticles D2 are not added, but 0.8 parts by weight of traditional Chinese medicine hemostatic active composition A2 and 3.2 parts by weight of blank PLGA micro / nanoparticles are added. All other parameters and steps are the same.
[0098] Comparative Example 3: Compared with Example 2, the difference is that 2 parts by mass of dopamine-modified chitosan B2 is replaced with 2 parts by mass of carboxymethyl chitosan, while the other parameters and steps are the same.
[0099] Comparative Example 4: Compared with Example 2, the difference is that 2.5 parts by mass of sodium oxidized alginate C2 is replaced with 2.5 parts by mass of sodium alginate, while the other parameters and steps are the same.
[0100] Comparative Example 5: Compared with Example 2, the difference is that 20 parts by weight of poloxamer 407 and 3 parts by weight of poloxamer 188 are not added, and the total amount is made up to 23 parts by weight with 0.01 mol / L phosphate buffer. All other parameters and steps are the same.
[0101] Test Example 1: Experimental description: This test case was used to verify the storage stability of a biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine in its packaged state, as well as its injectability, gelation performance at 37°C, gel integrity, and rheological properties after mixing.
[0102] Experimental steps: Components A, B, and C of the samples from Examples 1 to 3 were placed at 4°C for 7 days. The pH values on days 0 and 7 were recorded, and the appearance was observed. Components A, B, and C of the samples from Examples 1 to 3 were mixed in the corresponding volume ratios. After mixing, the mixture was loaded into a 1 mL syringe within 1 minute and injected through 21G, 23G, and 25G needles respectively. The injection speed was 1 mm / s, and the maximum injection force was recorded. Take 1 mL of the mixed liquid dressing and place it in a sample bottle. Test the gelation time using the inverted vial method under a 37℃ water bath. After the mixed liquid dressing gels at 37℃, place it in a 0.01 mol / L phosphate buffer solution at 37℃ for 2 hours and determine the mass retention rate. The storage modulus G′ and loss modulus G″ of the gel were tested using a rotational rheometer at a temperature of 37℃, a strain of 1%, and a frequency range of 0.1 to 10 Hz. The storage modulus G′ and loss modulus G″ at 1 Hz were recorded.
[0103] Experimental data: The test results are shown in Table 1.
[0104] Table 1: Data on dispensing stability, injectability after mixing, and gelation properties:
[0105] Experimental conclusion: Referring to Table 1, after being stored at 4°C for 7 days, components A, B, and C of the samples from Examples 1 to 3 showed minimal pH changes and no stratification, precipitation, or irreversible agglomeration. These results indicate that repackaging can reduce storage instability issues caused by premature contact between the traditional Chinese medicine hemostatic active composition, polysaccharide materials, and calcium chloride, making it suitable for liquid dressings mixed immediately before use.
[0106] The samples from Examples 1 to 3, after mixing, could all be dispensed using 21G, 23G, and 25G needles and formed a gel at 37°C. With increasing component content, the maximum injection force increased, the gelation time shortened, and the 2-hour mass retention rate improved. This trend is consistent with the increased content of polysaccharide materials, poloxamer, and drug-loaded PLGA micro / nanoparticles in the formulation, while all data remain within the reasonable range for the same liquid dressing system.
[0107] See attached document Figure 1In Examples 1 to 3, the storage modulus G′ curves in the range of 0.1–10 Hz all increased with increasing frequency, indicating that the mixed gel samples had a measurable elastic response. Example 3 had a higher storage modulus and a correspondingly higher injection force; Example 2 had a relatively coordinated injection force, gelation time, mass retention rate, and rheological response, and could be used as a base sample for subsequent hemostasis, release, and adhesion performance tests.
[0108] Test Example 2: Experimental description: This test case is used to verify the performance differences between the liquid dressings of Example 2 and Comparative Examples 1 to 3 in terms of in vitro coagulation, release of active ingredients, and wet tissue adhesion.
[0109] Experimental steps: Components A, B, and C of Examples 2, 1, 2, and 3 were mixed in the corresponding volume ratios to obtain the liquid dressings to be tested. Fresh anticoagulated whole blood was taken and recalcified with a calcium chloride solution of 0.1 mol / L. The volume ratio of anticoagulated whole blood to calcium chloride solution was 9:1. The test liquid dressing was brought into contact with the recalcified whole blood at 37°C, and the time it took for the blood to change from a flowing state to a non-flowing state was recorded. The liquid dressing to be tested was contacted with recalcified whole blood at 37°C for 5 minutes. Purified water was added to dissolve the uncoagulated red blood cells. After centrifugation, the supernatant was collected, and the absorbance was measured at a wavelength of 540 nm. The whole blood coagulation index was then calculated. The mixed liquid dressings of Example 2 and Comparative Example 2 were placed in phosphate buffer solution at pH 6.5 and temperature 37°C. Samples were taken at 1h, 24h and 72h, and the cumulative release rate of the active ingredients of the traditional Chinese medicine was determined by ultraviolet-visible spectrophotometry. The mixed liquid dressings of Example 2 and Comparative Example 3 were sandwiched between two pieces of moist pigskin with a contact area of 20 mm × 20 mm. They were placed at 37°C for 10 min, and the wet tissue adhesion strength was determined by the overlap shearing method with a tensile speed of 10 mm / min.
[0110] Experimental data: The in vitro hemostatic properties and wet tissue adhesion properties are shown in Table 2, and the release properties of the active ingredients are shown in Table 3. Each test was performed in triplicate, and the results are expressed as mean ± standard deviation.
[0111] Table 2: Data on in vitro hemostatic properties and wet tissue adhesion properties:
[0112] Table 3: Cumulative Release Rate Data of Active Ingredients
[0113] Experimental conclusion: Referring to Table 2, the in vitro coagulation time of Example 2 was 68.4 s, and the whole blood coagulation index was 22.8%, both lower than those of Comparative Example 1. In Comparative Example 1, without the addition of the traditional Chinese medicine hemostatic active composition and drug-loaded PLGA micro / nanoparticles, the coagulation time increased to 209.7 s, and the whole blood coagulation index rose to 58.6%. These results indicate that the traditional Chinese medicine hemostatic active composition participates in the recalcified whole blood coagulation process, contributing to improved in vitro hemostatic performance of the mixed liquid dressing.
[0114] Referring to Table 3, the cumulative release rates of Example 2 at 1h, 24h, and 72h were 16.8%, 39.7%, and 58.3%, respectively, while those of Comparative Example 2 were 43.2%, 69.4%, and 86.6%, respectively. Comparative Example 2, which used the direct addition of the traditional Chinese medicine hemostatic active composition, had a higher early release rate; Example 2, which used drug-loaded PLGA micro / nanoparticles, had a more gradual release process, which was beneficial in reducing early concentrated release.
[0115] See attached document Figure 2 In both Example 2 and Comparative Example 2, the 1-hour release solutions showed absorption responses in the 270–330 nm range. Comparative Example 2 exhibited a higher overall absorbance, consistent with the higher cumulative release rate observed in Table 3. Referring to Table 2, in Comparative Example 3, replacing dopamine-modified chitosan with carboxymethyl chitosan reduced the wet tissue adhesion strength from 21.6 kPa to 7.6 kPa, indicating that dopamine-modified chitosan significantly contributes to adhesion to wet tissue surfaces.
[0116] Test Example 3: Experimental description: This test case is used to verify the performance differences of the liquid dressings after mixing Example 2 with Comparative Examples 4 to 5 in terms of gel stability, retention on moist tissue surfaces, and hemostatic stability in ex vivo tissues.
[0117] Experimental steps: Components A, B, and C of Examples 2, 4, and 5 were mixed in the corresponding volume ratios to obtain the liquid dressings to be tested. Take the liquid dressing to be tested and gel it at 37℃, record the initial mass, and then place the gel in simulated wound exudate at 37℃ and pH 6.8. Remove it after 2 hours, 6 hours and 24 hours, absorb the surface liquid and weigh the remaining mass, and calculate the mass retention rate. The test liquid dressing was applied to the surface of a moist pigskin at a 45° angle and placed at 37°C for 10 min. Simulated wound exudate was used to flush the dressing at a flow rate of 5 mL / min for 10 min. The sample residue rate and shedding were recorded after flushing. The hemostasis stability was evaluated using an isolated porcine liver hemorrhage model. A wound with a length of 10 mm and a depth of 3 mm was prepared on the surface of an isolated porcine liver. The test liquid dressing was applied to the wound, and the hemostasis time, bleeding amount within 5 minutes and dressing fall-off were recorded. Gel samples were collected after being treated with simulated wound exudate for 6 hours. Frequency scanning was performed using a rotational rheometer at a test temperature of 37℃, a strain of 1%, and a frequency range of 0.1–10 Hz. The changes in storage modulus G′ were recorded.
[0118] Experimental data: The gel stability, wound retention, and hemostatic stability are shown in Tables 4 and 5. Each test was performed in triplicate, and the results are expressed as mean ± standard deviation.
[0119] Table 4: Data on gel stability and wound retention:
[0120] Table 5: Hemostasis data of the isolated porcine liver hemorrhage model:
[0121] Experimental conclusion: Referring to Table 4, the mass retention rate of Example 2 after 24 hours in simulated wound exudate was 81.7%, compared to 49.8% for Comparative Example 4 and 26.4% for Comparative Example 5. In Comparative Example 4, the gel retention capacity decreased after sodium alginate was replaced with sodium alginate; in Comparative Example 5, the integrity of the gel in the exudate was further reduced after poloxamer 407 and poloxamer 188 were removed.
[0122] Referring to Tables 4 and 5, the residual rate of Example 2 after dynamic rinsing was 88.5%, the hemostasis time in the isolated porcine liver model was 74.8 s, and the bleeding volume within 5 min was 0.46 g. Comparative Examples 4 and 5 showed local detachment or displacement after rinsing, prolonged hemostasis time, and increased bleeding volume, indicating that the retention state of the gel on the surface of moist tissue affects wound coverage and hemostatic stability.
[0123] See attached document Figure 3 After 6 hours of treatment with simulated wound exudate, the storage modulus G′ curve of Example 2 was higher than that of Comparative Example 4 and Comparative Example 5 in the range of 0.1–10 Hz, corresponding to the mass retention rate and flushing residue results in Table 4. This result indicates that oxidized sodium alginate helps maintain the gel structure, and poloxamer 407 and poloxamer 188 facilitate gel formation and wound retention at 37°C; the combination of these two ingredients further enhances gel integrity.
[0124] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine, characterized in that, Raw materials comprising the following parts by weight: Traditional Chinese medicine hemostatic active composition: 0.5 parts to 10 parts; Drug-loaded PLGA micro / nanoparticles: 1 to 8 parts; Dopamine-modified chitosan: 0.5 to 4 parts; Poloxamer 407: 12 to 25 servings; Polosham 188: 1 to 5 servings; Glycerin: 1 to 6 parts; Sodium alginate oxide: 0.5 to 5 parts; Tannic acid: 0.1 to 2 parts; Calcium chloride: 0.05 parts to 1 part; Phosphate buffer: 34 to 83.35 parts; The total mass fraction of the raw materials is 100 parts; The traditional Chinese medicine hemostatic active composition comprises the following components in parts by weight: Bletilla striata polysaccharide: 15-45 parts; Total saponins of Panax notoginseng: 8 to 30 parts; Total tannins from Sanguisorba officinalis: 5 to 20 parts; Typhae Flavonoids: 3 to 15 parts; Platycladus orientalis leaf flavonoids: 2 to 12 parts; Agrimonia pilosa extract: 2 to 12 parts; The drug-loaded PLGA micro / nanoparticles are PLGA micro / nanoparticles loaded with the hemostatic active composition of the traditional Chinese medicine.
2. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 1, characterized in that, The biomaterial self-adhesive hemostatic dressing is in a three-component form, comprising component A, component B, and component C. Component A, component B, and component C are mixed to obtain the biomaterial self-adhesive hemostatic dressing, wherein: Component A comprises the traditional Chinese medicine hemostatic active composition, the drug-loaded PLGA micro / nanoparticles, the dopamine-modified chitosan, the poloxamer 407, the poloxamer 188, the glycerol, and the phosphate buffer. Component B comprises the oxidized sodium alginate, the tannic acid, and the phosphate buffer solution; Component C comprises the calcium chloride and the phosphate buffer.
3. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 2, characterized in that, Component A, component B, and component C are prepared and mixed under the following conditions: The concentration of the phosphate buffer solution is 0.005 mol / L to 0.02 mol / L; Component A is obtained by stirring at 0℃~10℃ for 0.5h~3h; Component B is obtained by stirring at 0℃~10℃ for 0.5h~3h; Component C is a calcium chloride solution with a mass concentration of 1.55% to 9.33%; The volume ratio of component A, component B and component C is 1:(0.5-1.5):(0.05-0.3), the mixing time is 1 min to 3 min, and the pH after mixing is 5.8 to 7.
2.
4. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 1, characterized in that, The Bletilla striata polysaccharide was prepared by the following steps: Take Bletilla striata, grind it into powder, and pass it through a 60-100 mesh sieve; The pulverized and sieved Bletilla striata medicinal material is mixed with purified water at a mass ratio of 1:(6-20), and extracted at 60℃-90℃ for 1-3 hours, 1-3 times, and filtered to obtain Bletilla striata medicinal material filtrate. The filtrate of Bletilla striata was concentrated under reduced pressure at 40℃~50℃ to 1 / 5~1 / 3 of the volume of the filtrate to obtain a concentrated Bletilla striata extract. Add 95% ethanol to the concentrated Bletilla striata extract to make the final ethanol volume fraction 60%–80%. Let it stand at 2℃–8℃ for 6h–24h, centrifuge, collect the Bletilla striata precipitate, and dry the precipitate at 40℃–50℃ for 6h–10h to obtain the Bletilla striata polysaccharide.
5. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 4, characterized in that, The hemostatic composition of traditional Chinese medicine is prepared by the following steps: Take Panax notoginseng, Sanguisorba officinalis, Typha pollen, Platycladus orientalis leaves and Agrimonia pilosa herbs respectively, pulverize them and pass them through a 60-100 mesh sieve; The pulverized and sieved Panax notoginseng, Sanguisorba officinalis, Typha pollen, Platycladus orientalis leaves, and Agrimonia pilosa herbs were respectively mixed with an ethanol aqueous solution with a volume fraction of 30% to 80% at a mass ratio of 1:(6 to 20), and extracted at 40℃ to 80℃ for 1 to 4 hours, 1 to 3 times, and filtered to obtain Panax notoginseng filtrate, Sanguisorba officinalis filtrate, Typha pollen filtrate, Platycladus orientalis leaf filtrate, and Agrimonia pilosa filtrate, respectively. The filtrate of Panax notoginseng, the filtrate of Sanguisorba officinalis, the filtrate of Typha pollen, the filtrate of Platycladus orientalis leaf, and the filtrate of Agrimonia pilosa were concentrated under reduced pressure at 40℃ to 55℃, and dried at 40℃ to 55℃ for 6h to 10h, respectively, to obtain the total saponins of Panax notoginseng, the total tannins of Sanguisorba officinalis, the flavonoids of Typha pollen, the flavonoids of Platycladus orientalis leaf, and the extract of Agrimonia pilosa. The Bletilla striata polysaccharide, Panax notoginseng total saponins, Sanguisorba officinalis total tannins, Typha orientalis flavonoids, Platycladus orientalis leaf flavonoids and Agrimonia pilosa extract are mixed for 30 min to 60 min to obtain the traditional Chinese medicine hemostatic active composition.
6. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 1, characterized in that, The dopamine-modified chitosan was prepared by the following steps: Carboxymethyl chitosan and MES buffer solution with a concentration of 0.05 mol / L to 0.2 mol / L were mixed at a mass ratio of 0.5:99.5 to 3.0:97.0 to prepare a carboxymethyl chitosan solution with a mass concentration of 0.5% to 3.0%. Adjust the pH of the carboxymethyl chitosan solution to 4.5–6.0, and purge with N2 for 10–30 minutes; Dopamine hydrochloride is added to the carboxymethyl chitosan solution after N2 purging, wherein the mass ratio of dopamine hydrochloride to carboxymethyl chitosan is 0.05 to 0.5:1; 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added, with the molar ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and dopamine hydrochloride being (0.8-1.5):(0.8-1.5):
1. The mixture was reacted at 15℃-35℃ in the dark for 6-24 hours to obtain a dopamine-modified chitosan reaction solution.
7. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 6, characterized in that, The dopamine-modified chitosan reaction solution is processed through the following steps: The dopamine-modified chitosan reaction solution was placed in a dialysis bag with a molecular weight cutoff of 3500 Da to 14000 Da, and dialyzed with purified water for 24 h to 72 h to obtain dopamine-modified chitosan dialysis solution. The volume ratio of the purified water to the dopamine-modified chitosan reaction solution is 50:1 to 100:1, and the purified water is replaced every 6 to 12 hours. The dopamine-modified chitosan dialysis solution was pre-frozen at -60℃ to -20℃ for 6h to 24h and freeze-dried for 12h to 36h to obtain the dopamine-modified chitosan.
8. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 1, characterized in that, The oxidized sodium alginate is prepared by the following steps: Sodium alginate and purified water were mixed at a mass ratio of 0.5:99.5 to 2.5:97.5 to prepare a sodium alginate solution with a mass concentration of 0.5% to 2.5%. Adjust the pH of the sodium alginate solution to 6.0–7.0; Sodium periodate was added to the sodium alginate solution after pH adjustment, wherein the molar ratio of sodium periodate to sodium alginate uronic acid units was 0.05 to 0.25:1, and the reaction was carried out at 15°C to 30°C in the dark for 2 to 10 hours. Ethylene glycol is added to terminate the reaction, wherein the molar ratio of ethylene glycol to sodium periodate is 1.5 to 3:1, and the reaction is terminated at a time of 0.5 to 2 hours to obtain an oxidized sodium alginate reaction solution. The sodium alginate oxidized reaction solution was placed in a dialysis bag with a molecular weight cutoff of 3500 Da to 14000 Da, dialyzed with purified water for 24 h to 72 h, and then freeze-dried for 12 h to 36 h to obtain the sodium alginate oxidized solution.
9. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 1, characterized in that, The drug-loaded PLGA micro / nanoparticles were prepared by the following steps: Take the aforementioned traditional Chinese medicine hemostatic active composition and mix it with purified water at a mass ratio of 1:99 to 5:95 to prepare an internal aqueous phase with a mass concentration of 1% to 5%. Mix PLGA with ethyl acetate to prepare an organic phase with a mass concentration of 2% to 6%; The mass ratio of the traditional Chinese medicine hemostatic active composition to the PLGA is 1:10 to 1:2, and the volume ratio of the internal aqueous phase to the organic phase is 1:10 to 1:
2. The aqueous phase is added to the organic phase, and ultrasonic emulsification is performed under ice bath conditions. The ultrasonic power is 100W to 300W, and the ultrasonic emulsification time is 5min to 15min to obtain the primary emulsion.
10. The biomaterial self-adhesive hemostatic dressing based on hemostatic active ingredients of traditional Chinese medicine according to claim 9, characterized in that, The colostrum is processed through the following steps: The primary emulsion was added to a polyvinyl alcohol aqueous solution with a mass concentration of 0.5% to 3.0%, wherein the volume ratio of the polyvinyl alcohol aqueous solution to the organic phase was 5:1 to 20:
1. Shear emulsification was carried out under ice bath conditions at a rotation speed of 6000 rpm to 14000 rpm and a shear emulsification time of 0.5 h to 2 h to obtain a secondary emulsion. The re-emulsion was stirred at 25℃~30℃ for 2h~6h, then centrifuged at 8000rpm~12000rpm for 10min~20min. The supernatant was discarded, the precipitate was collected, and the precipitate was washed three times with purified water and freeze-dried for 12h~36h to obtain the drug-loaded PLGA micro / nanoparticles.
